Anisotropic Fracture Characteristics of Coal Under Static and Dynamic Loadings - Wang, Wei (Curtin University, 2025)
This study commences with the mesoscopic fracture mechanism of coal burst, focusing on fracture properties of coal under static and dynamic loadings. Employing a multi-faceted approach, including theoretical analysis, laboratory tests, and numerical simulations, the anisotropy and rate-dependency of fracture behaviors of coal are investigated after regarding it as a transversely isotropic body. It is expected that this research can provide a theoretical foundation for understanding coal bursts and offers insight for disaster prevention.